Timing, Recurrence, and Effects of Fixed Asset Revaluation: Evidence from Bangladesh - Rahman, Md. Tahidur; Hossain, Syed Zabid; Haque, Md. Anwarul (International Journal of Economics and Financial Issues, 2021)
This study intended to explore when and how often fixed asset revaluation (FAR) is practiced in Bangladesh and explain the impacts of FAR on net asset value (NAV), stock prices, and debts of companies. Based on 175 listed companies on the Dhaka Stock Exchange, this study found increasing use of the revaluation model where the textile industry witnessed the highest number of revaluations. Most of the listed companies were irregular revaluer, and they performed FAR during the bull market in 2010. Most newly listed companies did it just before their initial public offerings (IPO). The results of the Wilcoxon signed-rank test imply that the changes in NAV, stock prices, and total debts after revaluation were statistically significant. This study found evidence of enhancing debt capacity and stock prices of several companies through improved NAV. The findings will assist regulators to recognize the consequence of revaluation and enable them to take an appropriate stance for controlling abusive and creative reporting. The study will also make investors cautious about companies with revaluation induced assets. This study suggests that companies practicing the revaluation model should perform FAR on regular intervals to reduce information asymmetry about assets’ value and thus help improve investors’ confidence. Keywords: Fair value accounting, IAS 16, PP&E, Bull-bear market, Information asymmetry, NAV JEL Classifications: G1, G11, M41, M48 DOI: https://doi.org/10.32479/ijefi.10828